Water supply and wastewater disposal in developing countries (Bangkok, 1971)
Water supply and wastewater disposal in developing countries discusses various approaches to municipal wastewater management in order to protect both public health and the environment, with the major focus being on waterborne diseases. Developing countries can be divided into two main categories, i.e. countries in transition with higher growth rates where industrialisation and urbanisation are taking place rapidly, and countries with slower growth rates. It is important, therefore, that approaches should be tailor-made and site-specific
Kỹ thuật xử lý nước thải và nước cấp nâng cao
Keywords: Water supply,Wastewater technology,Environmental engineering